Patient factors that affect trust in physicians: a cross-sectional study - Agnus M. Kim; Jaekyoung Bae; Sungchan Kang; Yeon-Yong Kim; Jin-Seok Lee (BMC Family Practice, 2018)
Abstract Background While trust in physicians has been rigorously investigated regarding its concept, measurement, and factors, the studies have mainly focused on the attributes of the physicians. This approach can lead to a limited understanding of trust in physicians as trust is based on the relationship, an interaction of both parties: patients and physicians. This study aimed to investigate the factors for trust in physicians among the Koreans by focusing on patients’ traits which are related to their subjective perceptions. Methods A web-based survey was conducted between August and September 2016 among 1000 Korean adults aged 18 to 59 years. Survey participants were selected by a proportionate quota sampling based on age, sex and place of residence. The t-test and analysis of variance (ANOVA) were performed to examine the difference in trust in physicians among the different groups in each variable of patient characteristics. An ordinal logistic regression model was employed to examine the association between trust in physicians and patient attributes. Results Negative health-related traits, such as stress and low self-rated health, were likely to lower trust in physicians, and women were less likely to trust physicians. The negative attitudes toward the current health care system were strongly associated with low trust in physicians. Meanwhile, recent experience of hospitalization or outpatient visit was positively associated with trust in physicians, and experience of not being able to use health facilities showed no significant association. These results suggest that trust in physicians is more likely to be lowered by negative perception than by the objective conditions or experience. Conclusion In investigating the factors for trust in physicians, the patients’ predispositions, which make them less likely to trust physicians, should be considered. The attributes of the patients in Korea, which could negatively affect trust in physicians, need to be investigated in consideration of the recent changes in patient-physician relationships and the medical environment in Korea.